Negotiating the Future: The Iwakura Mission to the United States and Britain (1871-1873) - Ali, Afrah Mohammed (Thi Qar Arts Journal, 2025)
Attempting to study and analyze the entire Iwakura Mission, which was sent by the Japanese government between 1871 and 1873 to the United States and European countries (12 European countries) and visited a total of 120 cities during the mission, in one research paper is certainly an ambitious goal. However, due to the limitations on the number of pages allowed for publishing research, I will focus on two specific aspects of the Iwakura Mission: first, the visit of the Japanese diplomatic delegation to the United States and Great Britain, and second, what Japan learned from these two Western countries and how it applied the knowledge it acquired in its national context. I believe it is extremely important and interesting to compare the concepts learned by Japanese politicians from their American and British counterparts, as the United States and Great Britain represented the main liberal model for the Japanese nation at that time. Research Problem: Did the mission succeed in its plans that were prepared before traveling? Was Japan’s situation at that time conducive to negotiating with the strongest and largest Western powers, namely the United States and Great Britain? Did Japan possess the political experience to enter into negotiations with Western powers regarding treaty revisions? Was the idea of sending a mission to Europe a purely Japanese thought or a result of the influence of Japanese officials and decision-makers by Western minds working in Japan as advisors to the modern Meiji government? Or was it influenced by previous Japanese missions to Europe in the late Tokugawa period? Research Hypothesis: The idea of the mission was a natural outcome of the convergence and integration of pure Japanese thought with Western thought in both direct and indirect ways. This was due to the Japanese leaders’ conviction of Western development and the vast gap between the West and Japan through real observations during their visits to Western countries, and their admiration for the development of Western thought by European advisors who were attracted to Japan in the early years of the Meiji era. All of this will be clarified in the course of the research.